Presence and development of diabetic retinopathy in 153 238 patients with type 2 diabetes in the Danish Registry of Diabetic Retinopathy. Issue 2 (3rd October 2022) - Grauslund, Jakob; Pedersen, Frederik Nørregaard; Andersen, Nis; Andresen, Jens; Bek, Toke; Dinesen, Sebastian; Hajari, Javad; Heegaard, Steffen; Højlund, Kurt; Laugesen, Caroline Schmidt; Kawasaki, Ryo; Möller, Sören; et al.
Abstract: Purpose: The purpose of the study was to evaluate the prevalence and incidence of diabetic retinopathy (DR) along with associated markers in patients with type 2 diabetes in the Danish DR‐screening programme. Methods: We included all persons with type 2 diabetes in the Danish Registry of Diabetic Retinopathy, who had attended at least one episode of DR screening in 2013–2018. DR was classified as levels 0–4 indicating increasing severity. Data were linked with various national health registries to retrieve information on diabetes duration, marital status, comorbidity and systemic medication. Results: Among 153 238 persons with type 2 diabetes, median age and duration of diabetes were 66.9 and 5.3 years and 56.4% were males. Prevalence and 5‐year incidences of DR, 2‐step‐or‐more progression of DR and progression to proliferative DR (PDR) were 8.8%, 3.8%, 0.7% and 0.2%, respectively. In multivariable models, leading markers of incident DR and progression to PDR were duration of diabetes (HR 1.98, 95% CI 1.87–2.09; HR 2.89, 95% CI 2.34–3.58 per 10 years of duration) and use of insulin (HR 1.88, 95% CI 1.76–2.01; HR 2.40, 95% CI 1.84–3.13), while the use of cholesterol‐lowering medicine was a protecting marker (HR 0.87, 95% CI 0.81–0.93; HR 0.70, 95% CI 0.52–0.93). From 2013 to 2015, 3‐year incidence rates of PDR decreased from 1.22 to 0.45 events per 1000 person‐years. Conclusion: Nationally, among Danish individuals with type 2 diabetes attending DR screening, we identified duration of diabetes and use of insulin as the most important predictor for the development of DR, while cholesterol‐lowering medicine was a protective factor.